2007
DOI: 10.1007/bf03177403
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties of photo resist thin films

Abstract: Photo resist thin films have mainly been used and investigated for versatile applications of micro electronic mechanical systems because of its outstanding aspect ratio and attainable film thickness. An accurate structure properties derived from validated material characterization is required in engineering applications. In this work, dynamic responses of photo resist thin films are tested by a nanoindentation in association with a dynamic mechanical analysis, where the thin film is coated on a silicon wafer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Let the contact strain ε c and the contact stress σ c be calculated according to equations ( 6) and (7), figure 4 can then be redrawn as figure 5 so as to demonstrate the experimental relationship between ε c and σ c .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let the contact strain ε c and the contact stress σ c be calculated according to equations ( 6) and (7), figure 4 can then be redrawn as figure 5 so as to demonstrate the experimental relationship between ε c and σ c .…”
Section: Resultsmentioning
confidence: 99%
“…In the past years various efforts have been made to determine the mechanical properties of polymers, and photoresists in particular [6][7][8][9][10], yielding comprehensive knowledge about the material properties of thermoplastic polymers used in micro-system technology, e.g. PMMA, SU-8, Ormocomp and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films have found increasing applications in many advancing technologies [1][2][3][4][5][6]. To increase the reliability, lifespan and structural stability of functional thin films and thin film structures, a better characterization of mechanical properties such as Poisson's ratio and Young's modulus of elasticity, which play an important role in the mechanical performance of thin films, is often found to be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the viscoelasticity of the transverse line, grid, and square patterns as a function of the frequency increased significantly at higher temperatures because of the enhanced viscoelastic characteristics of the surrounding layers, such as the BT core and PSR. However, the longitudinal line pattern showed little change with frequency even at 90 °C, because the analytical equation of this pattern is independent of the surrounding layers (see equation (13)).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to simulate the warpage of PCB simply and accurately, equivalent modeling of Cu micro-patterns for each shape, including the effect of surrounding layers such as BT core and PSR layers, is necessary. Furthermore, raw materials for PCB such as woven glass fabric/ BT (bismaleimide triazine), composite laminate (BT core), and photoimageable solder resist (PSR) have thermo-viscoelasticity properties that change the modulus depending on time and temper ature [13,14]. For this reason, analysis of the viscoelastic thermo-mechanical deformation behavior of multi-layered PCB under the reflow process (the maximum temperature is 260 °C) is essential for the accurate prediction of the warpage in a multi-layered PCB.…”
Section: Bi-directional Homogenization Equivalent Modeling For the Pr...mentioning
confidence: 99%